Neurolytic Lumbar Sympathectomy In Ischemic Vascu/ar Disease Of Lower Extremity: (An Evaluation of 3 Cases) (Annals of Medical Research, 2021)
None
Keywords: s : Neurolytic sympathetic biockade, peripherai vascular disease, phenol.